Oestrogen and progesterone receptors in the uterine wall of bitches with cystic endometrial hyperplasia/pyometra - Dhaliwal, G. K.; England, G. C. W.; Noakes, D. E. (Wiley, 1999)
Fresh samples of uterine wall and peripheral plasma were obtained from 13 bitches of different breeds when they were treated for cystic endometrial hyperplasia/pyometra by ovariohysterectomy. The plasma samples were assayed for progesterone and 17β‐oestradiol, and the tissue samples were examined histopathologically and for the presence of oestrogen and progesterone receptors by an immunocytochemical method. The immunoreactivity was scored semiquantitatively, taking into account both the intensity and distribution of the specific staining of the receptors, by using a simplified scoring system. The scores for both oestrogen and progesterone receptors in the glandular epithelium were much lower, and in the endometrial stroma a mean (sd) score for oestrogen receptors was 46.0 (44.7) compared with 0 in comparable endometrial tissues from normal bitches at the same stage of the oestrous cycle.